HUBUNGAN KECERDASAN EMOSIONAL DENGAN ETIKA KOMUNIKASI MAHASISWA DI UNIVERSITAS MUSAMUS MERAUKE - Antonius Nggewaka (Universitas Musamus, Merauke, Papua, 2015)
Communication ethics based on high emotional intelligence can encourage the achievement of quality academic atmosphere. This aim of the research was to find out the relationship between students’ emotional intelligence with communication ethics in creating academic atmosphere.This research was a correlational descriptive study conducted in Musamus University of Merauke. The samples consisted of 67 students, lectures, and head of university. The research used mixed methods. The result of the research indicate that there is significant relationship between students’ emotional intelligence and their communication ethich in creating academic atmosphere (P-values = 0.000).Emotional intelligence dimension which give the most significant influence is social skill or to make relationship with other people, i.e 74.9%, and the least significant influences is managing emotion dimension or to manage emotion, i.e 20.9%. simultaneously, the influence of emotional intelligence on communication ethics is 69.1% and the remaining 30.9% is influenced by other factors.In creating an academic atmosphere the role of university is not only to improve students IQ (intelligence quotient), but also to improve the EQ (emotional quotien).